2022
DOI: 10.3866/pku.whxb202208008
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Key Materials and Technologies for Secondary Batteries

Abstract: The storage and utilization of energy is one of the important topics in the development of science and technology, especially regarding secondary batteries, which are efficient electrical-/chemical-energy-converting devices. This review systematically introduces the important research progress made in the context of secondary batteries, starting from their development and leading to the introduction of related basic theoretical knowledge. The current research on secondary batteries that are based on different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Since the introduction of the Segment Anything Model (SAM), there has been a wave of attempts to develop a more accurate and robust medical image segmentation system with the utilization of SAM [11,32,16,26,28,18]. Recent work has shown that SAM alone, without further fine-tuning and/or adaptation, often delivers unsatisfactory results for medical image segmentation tasks [11,32]. To utilize SAM more effectively, Ma et al [16] proposed to fine-tune SAM using labeled images.…”
Section: Sam For Medical Image Segmentationmentioning
confidence: 99%
“…Since the introduction of the Segment Anything Model (SAM), there has been a wave of attempts to develop a more accurate and robust medical image segmentation system with the utilization of SAM [11,32,16,26,28,18]. Recent work has shown that SAM alone, without further fine-tuning and/or adaptation, often delivers unsatisfactory results for medical image segmentation tasks [11,32]. To utilize SAM more effectively, Ma et al [16] proposed to fine-tune SAM using labeled images.…”
Section: Sam For Medical Image Segmentationmentioning
confidence: 99%
“…As a result, sodium-ion batteries (SIBs) are becoming the most promising alternative due to their lower cost, more widespread global reserves and higher storage capacity. [6][7][8][9][10][11] Indeed, the performance of cathode and anode materials is crucial for energy storage devices. An excellent electrode material must satisfy several including low insertion potential, relatively stable structure, high electronic and ionic conductivity, and high compatibility with the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, rechargeable batteries have developed into important energy storage and functional devices. Among them, metal ion batteries represented by lithium-ion batteries (LIBs), sodium-ion batteries (SIBs), potassium-ion batteries, zinc-ion batteries, magnesium-ion batteries, etc have been developed considerably [7][8][9][10][11][12]. As early as the late 1970s, SIBs and LIBs were researched almost simultaneously, but in 1991, LIBs had been commercialized, while the development of SIBs was once slow or even at a standstill [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%